1997
DOI: 10.1159/000147960
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lung, Kidney and Skin in the Brushtail Possum, <i>Trichosurus vulpecula</i>

Abstract: The thyroid gland is not present at birth in marsupials and thyroid function begins during the latter half of pouch life. The hormonal output of the thyroid gland is important for normal development. In this study the structure of the lung, kidney and skin of the developing possum was examined and the structural development of these three organs was described. The lung of the newborn brushtail possum was functional and continued to develop during pouch life, alveolar formation beginning at day 39 and concludin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 5 publications
4
13
0
1
Order By: Relevance
“…Lung development is characteristically slow in marsupials (Krause & Leeson, 1975; Gemmell, 1986; Buaboocha & Gemmell, 1997; Burri et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Lung development is characteristically slow in marsupials (Krause & Leeson, 1975; Gemmell, 1986; Buaboocha & Gemmell, 1997; Burri et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Hughes and Hall (1984) described the prenatal brushtail possum lungs as having small blood vessels and cuboidal epithelium lining the developing bronchi. Buaboocha and Gemmell (1997) also described the brushtail possum lung and stated that it had squamous epithelium and surfactantsecreting cells. The lung sections in this study were similar.…”
Section: Discussionmentioning
confidence: 99%
“…In some marsupial species, such as the American opossum (Krause & Leeson, 1973) and bandicoot (Gemmell, 1986), alveolar development coincides with the time at which the young first leave the pouch. Buaboocha & Gemmell (1997) recorded that alveolar formation began in the lung of the brushtail possum at 39 days, concluding at 113 days, and that the lung had an adult appearance at 129 days. Fletcher & Selwood (2000) found that pouch young of this species are permanently attached to the teat for 70 days, soon after which the teat is voluntarily released.…”
Section: Discussionmentioning
confidence: 99%
“…Those which have been published have placed emphasis on the postnatal development of alveoli. These include studies of the American opossum, Didelphis virginiana (Sorokin, 1962;Krause & Leeson, 1973, 1975Krause et al 1976), Australian eastern native cat, Dasyurus viverrinus (Hill & Hill, 1955), Australian northern native cat, Dasyurus hallucatus (Gemmell & Nelson, 1988), the red-necked wallaby, Macropus rufogriseus (Walker & Gemmell, 1983), the tammar wallaby, Macropus eugenii (Runciman et al 1996(Runciman et al , 1999, the marsupial bandicoot, Isoodon macrourus (Gemmell & Little, 1982;Gemmell, 1986), and the brushtail possum, Trichosurus vulpecula (Gemmell & Nelson (1988); Buaboocha & Gemmell, 1997). Only Krause & Leeson (1973, 1975 provide some information concerning the development of bronchi, and Tucker (1974) makes brief mention of the trachea and bronchi of the brushtail possum and koala ( Phascolarctos cinereus ).…”
Section: Introductionmentioning
confidence: 99%